Principal Leadership, Teacher Professionalism, Community Participation, and Educational Quality: A Mixed-Methods Study of Public Elementary Schools in Welahan District - Sayyidati Vivi Fitroh; Ahmad Haryadi; Sri Utaminingsih; Lipolelo Thamae (Elicit Journal of Education Studies, 2026)
Purpose: This study examined the influence of principal leadership, teacher professionalism and community participation on educational quality in public elementary schools in Welahan District, Indonesia, while exploring how principals support teacher development and stakeholder relationships. Methodology: A convergent parallel mixed-methods design was adopted. Quantitative data were collected from 80 teachers selected through proportionate random sampling using a five-point Likert questionnaire and analysed with multiple linear regression. Qualitative data were obtained through semi-structured interviews with principals and teachers and analysed using Miles and Huberman’s interactive model. Both datasets were integrated during interpretation. Results: Principals supported teacher professionalism through academic supervision, coaching, professional development programmes, motivational support and school policies. They also strengthened stakeholder relationships through transparent communication, collaboration with school committees, and partnerships with community institutions. Principal leadership did not significantly predict educational quality directly (β = .182, p = .054). Teacher professionalism (β = .452, p < .001) and community participation (β = .266, p = .007) significantly predicted educational quality. Together, the three variables explained 38.6% of the variance in educational quality (R² = .386, F = 15.912, p < .001). Novelty and Contribution: The study integrates quantitative and qualitative evidence to show that principal leadership is associated with educational quality, primarily through strengthening teacher professionalism and stakeholder engagement. Social and Practical Implications: Educational quality may be strengthened by sustained investment in teacher professional development, participatory school leadership, and structured community involvement to support continuous school improvement.